Resource and service discovery in SOAs: a P2P oriented semantic approach - Di Modica, Giuseppe; Tomarchio, Orazio; Vita, Lorenzo (Zielona Góra: Uniwersytet Zielonogórski)
An intense standardization process is favouring the convergence of grids and Service Oriented Architectures (SOAs). One of the benefits of such technological convergence is that grid resources and applications can be virtualized by services and offered through the SOA paradigm. In the broad and interoperable scenarios enabled by the SOA, involving the participation of several grid infrastructures across many administrative domains, service discovery can be a serious issue. In this paper we present a P2P-based infrastructure that leverages semantic technologies to support a scalable and accurate service discovery process.
Keywords: SOA; web service discovery; P2P; semantic; JXTA